Strain relaxation in indium gallium arsenide phosphide films on indium phosphide substrates - Wu, Xiaohua (My University, 2000)
Transmission electron microscopy (TEM), atomic force microscopy (AFM) and scanning electron microscopy (SEM) have been used to study the strain relaxation mechanisms in In1-x Gax Asy P 1-y films grown on (100) InP substrates using gas-source molecular beam epitaxy (MBE). Highly anisotropic strain relief behavior was found in 2% tensile strained In0.25 Ga0.75 As and In0.72 Ga0.28 P films. In the first stages of film growth, the strain in [01¯1] cross-section was relieved by twinning, while it occurred by cracking in the orthogonal [011] cross-section. In the In0.25 Ga0.75 As film cracking was a transitory phenomenon. Crack healing was observed in the 500 nm thick film. Cracks were observed to penetrate into the substrate and deviate from an (01¯1) to (11¯1) or (1¯1¯1) planes. A critical stress intensity argument was developed to explain substrate cracking. A dislocation analogue for a surface crack was developed to successfully account for the experimental value of the ratio of crack opening displacement to normal surface displacement associated with cracks in In0.72 Ga0.28 P films. The 90° partial dislocations were found to form prior to the formation of either cracks and or 60° dislocations in In0.25 Ga0.75 As films, which is consistent with the critical thickness and nucleation calculations. Elastic strain energy computations show that the 90° partial dislocations also provide the most effective relief of elastic strain energy for films with smaller thickness, while cracks are the most effective strain relaxation mechanism for thicker films. It has also been shown both experimentally and theoretically that the twin thickness increases with an increase in the film thickness. The free surface plays an important role in determining the equilibrium position of misfit dislocations in thin epitaxial films. The computations based on a force argument show that the core of the dislocation lies close to the interface when the film is softer than the substrate. On the other hand, when the film is elastically stiffer than the substrate, the core of the dislocation is predicted to lie at some distance from the interface in the softer substrate. This prediction agrees with the experimental observations that the 90° partial dislocations bounded by stacking faults are frequently observed to locate inside the InP substrate over a range of a few hundred angstroms. The composition modulation in In1-x Gax As y P1-y films was found to be associated with the chemical spinodal in this alloy. Films with compositions lying within the chemical spinodal at growth temperature show fine scale composition modulation contrast. The composition modulation scales with the size of the strain-induced surface facets.
Keywords: Materials Science and Engineering; Materials Science and Engineering